Mechanical characterization of cells and tissues by scanning acoustic microscopy and optical tweezers - Demirkan, İrem. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Cell and tissue mechanics has a vital role in several pathological and physiological processes. Mechanical perturbations produce numerous biological processes within a cell or a tissue, which can result in mechanical changes. Thus, examination of the underlying mechanical characteristics of biological surroundings is a promising and important research area for the diagnosis and prognosis of diseases, especially in cancer. To delve into this, we rst proposed the application of Scanning Acoustic Microscopy (SAM) for monitoring di usion of sodium ion, which is known to regulate bodily functions and biological processes, by time-dependent acoustic impedance measurements on the soft tissue-mimicking agarose phantom. We established a linear correlation between the alterations in the phantom concentration and its acoustic impedance distribution. The second question in this thesis was to whether establish a correlation between cumulative irradiation doses and the mechanical properties of the human teeth or not. Here, 320 MHz SAM in micrometer resolution was used to characterize the acousto-mechanical e ects on human teeth after radiation therapy application, which is applied to cure head and neck cancer patients. Apart from SAM, this thesis introduces a dual-beam optical tweezers study for the quanti cation of red blood cell deformability as a determinant factor to assess cell reactions to radiotherapy on the cell cortex level. These two imaging techniques were used to understand the mechanical variations in response to exterior stimuli in biological matter. For each experiment, this thesis revealed the advantages and disadvantages of these methods and the reasons behind the ndings from the physical and biological points of view.
Keywords: Cells -- Mechanical properties.; Microscopy.; Optical tweezers.